Quantity implicatures - Geurts, Bart (Cambridge University Press, 2010)
In recent years, quantity implicatures - a type of pragmatic inference - have been widely debated in linguistics, philosophy, and psychology, and have been subject to an enormous variety of analyses, ranging from lexical, syntactic, semantic, and pragmatic, to various hybrid accounts. In this first book-length discussion of the topic, Bart Geurts presents a theory of quantity implicatures that is resolutely pragmatic, arguing that the orthodox Gricean approach to conversational implicature is capable of accounting for all the standard cases of quantity implicature, and more. He shows how the theory deals with free-choice inferences as merely a garden variety of quantity implicatures, and gives an in-depth treatment of so-called 'embedded implicatures'. Moreover, as well as offering a comprehensive theory of quantity implicatures, he also takes into account experimental data and processing issues. Original and pioneering, and avoiding technical terminology, this insightful study will be invaluable to linguists, philosophers, and experimental psychologists alike